Sinergitas dan Kinerja Organisasi Perangkat Daerah (OPD) dalam Pelaksanaan Kebijakan Sektor Pertanian di Kabupaten Timor Tengah Utara - Dian Festianto; Marthen Patiung; Medan Yonathan Mael; Agustinus Longa Tiza (Fakultas Pertanian, Universitas Timor, 2019)
This study describes the synergy of the Regional Device Organization (OPD) in the implementation of the Sari Tani program as the flagship program of Timor Tengah Utara (TTU) regency, which is conducted with an analytical descriptive case study approach with the aim of establishing an alternative model in the acceleration policy of agricultural sector order to realize food sovereignty in TTU district. The size of synergy includes the intensity of coordination and synchronization between OPD from the formulation stage to the implementation of the policy. Primary data collection through interviews with stakeholders by using purposive sampling technique, to fulfillment the objectivity of the research community farmers interviewed as additional informants with cluster sampling techniques, while secondary data obtained through related institutions. Observation is also done to understand the attitude and behavior of research subjects. In order to improve internal validity, the author uses the triangulation method. The result of the research shows that the performance of the flagship program TTU Regent has not been optimal because the revolving funding is based on the result of the effort outside the flagship program. This is due to the low coordination between OPD resulting in overlapping the implementation level, while internally there is no control instrument field, in addition to the recruitment process of field assistants tends to be politicized, thus affecting the capability of field assistants. For that, the government needs to establish a special team to monitor in order to increase acceleration between OPD.